2009
DOI: 10.1016/j.actbio.2008.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Altered structural and mechanical properties in decellularized rabbit carotid arteries

Abstract: Recently, major achievements in creating decellularized whole tissue scaffolds have drawn considerable attention to decellularization as a promising approach for tissue engineering. Decellularized tissues are expected to have mechanical strength and structure similar to the native tissues from which they are derived. However, numerous studies have shown that mechanical properties change after decellularization. Often, tissue structure is observed by histology and electron microscopy, but the structural alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
114
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(122 citation statements)
references
References 68 publications
7
114
0
1
Order By: Relevance
“…This behavior can be ascribed to the presence of more abundant muscular components in the 1st and 2nd DEM cycle with respect to the two successive DEM cycles and to the resulting un-crimped collagen structure, as histologically observed. Referring to this latter point, it has been previously reported that decellularized rabbit carotid arteries were stiffer than native vessels, being probably related to the presence of un-crimped collagen in decellularized arteries (18). Therefore, it is possible to infer that both these conditions (i.e.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This behavior can be ascribed to the presence of more abundant muscular components in the 1st and 2nd DEM cycle with respect to the two successive DEM cycles and to the resulting un-crimped collagen structure, as histologically observed. Referring to this latter point, it has been previously reported that decellularized rabbit carotid arteries were stiffer than native vessels, being probably related to the presence of un-crimped collagen in decellularized arteries (18). Therefore, it is possible to infer that both these conditions (i.e.…”
Section: Discussionmentioning
confidence: 95%
“…The DEM approach has been proven as an effective method to obtain ECM-derived prosthetic grafts, which can support in vitro and in vivo cell adhesion and proliferation: acellular matrices are remodelled in living tissues and can function as urethra (13), small bowel (14), skeletal muscle (15), esophagus (16) and tracheal (17) substitutes. However, while many studies focused on the decellularized tissue biocompatibility, cell seeding and implantation potential, only few reported findings on relationships between tissue decellularization and the physical and mechanical properties of tissue (7,18).…”
Section: Decellularized Bovine Reinforced Vessels For Small-diameter mentioning
confidence: 99%
“…The two main features, characterizing collagen fiber organization, are its waviness and angular dispersion. Other factors that could determine the mechanical properties of the adventitia are collagen cross-linking, fiber density and glycoproteins (Williams et al 2009;Et-Taouil et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…11,[14][15][16][17][18][19][20][21][22][23][24] When tissues have been efficiently decellularized, the ECM-specific structural and functional components that remain (collagen, laminin, fibronectin, growth factors, etc.) are relatively well conserved across mammalian species and, therefore, do not evoke adverse immune reaction.…”
mentioning
confidence: 99%